2021
DOI: 10.3390/app112411691
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Technique for High-Gain CMOS Power Amplifier for 5G Applications

Abstract: In this study, a differential power amplifier (PA) with a high gain of over 30 dB by configuring a three-stage common source unit amplifier was designed. To ensure the stability of the high-gain differential PA, the analysis to apply the capacitive neutralization method to the differential common source PA was conducted. From the analysis, the required neutralized capacitance was quantitatively calculated from the estimated parasitic components of a power cell used in the PA. To verify the feasibility of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In this study, as shown in Figure 1, a capacitive neutralization technique was utilized to ensure stability in the high gain PA [18][19][20]. In Figure 3, the equivalent half-circuit of the common-source stage of Figure 1 is shown.…”
Section: Determination Of Neutralization Capacitor Valuesmentioning
confidence: 99%
“…In this study, as shown in Figure 1, a capacitive neutralization technique was utilized to ensure stability in the high gain PA [18][19][20]. In Figure 3, the equivalent half-circuit of the common-source stage of Figure 1 is shown.…”
Section: Determination Of Neutralization Capacitor Valuesmentioning
confidence: 99%